2016
DOI: 10.1002/stem.2427
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Induces RUNX2 Activity and Osteogenic Development from Human Pluripotent Stem Cells

Abstract: Pluripotent stem cells, both human embryonic stem cells (hESC) and induced pluripotent stem cells (iPSC), provide an important resource to produce specialized cells such as osteogenic cells for therapeutic applications such as repair or replacement of injured, diseased or damaged bone. hESCs and iPSCs can also be used to better define basic cellular and genetic mechanisms that regulate the earliest stages of human bone development. However, current strategies to mediate osteogenic differentiation of hESC and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…RUNX1 has been shown to play a role in haematopoiesis and haematopoietic function[19]. RUNX2 has been reported to be a key regulator required for osteogenic differentiation[20], while RUNX3 has been shown to be related to gastrointestinal tract development[21]. All three RUNX genes are associated with Smads and the TGF-β signalling pathway[22–24].…”
Section: Introductionmentioning
confidence: 99%
“…RUNX1 has been shown to play a role in haematopoiesis and haematopoietic function[19]. RUNX2 has been reported to be a key regulator required for osteogenic differentiation[20], while RUNX3 has been shown to be related to gastrointestinal tract development[21]. All three RUNX genes are associated with Smads and the TGF-β signalling pathway[22–24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the synthetic PSS/PAH system is not suitable for a clinical application as it was used here as a kind of reference system because of its known cytocompatibility . The other two systems were included due to the known osteogenic activity of fibrinogen and the inherent bioactivity of chondroitin sulfate toward proteins with heparin‐binding domains . Physical studies showed that the PSS/PAH multilayer system was well separated with intermediate wetting properties, opposing sign of charge of terminal PSS and PAH layers, which was also the case for BCS/FBG multilayer system.…”
Section: Discussionmentioning
confidence: 99%
“…6 hESC-RUNX2-YFP cells used to report differentiation into osteoprogenitors (OPs) were previously described. 10 Undifferentiated hPSCs were taken as the negative controls.…”
Section: Cell Linesmentioning
confidence: 99%
“…Real-time reverse-transcription polymerase chain reaction (RT-PCR) analysis was done as previously described. 10 Briefly, total RNA was extracted using Qiagen RNeasy Mini Kit (Qiagen, Valencia, California) and 1 μg of RNA was reverse transcribed into cDNA using SuperScript II Reverse Transcriptase (ThermoFisher Scientific), based on the manufacturer's instructions. Quantitative real-time RT-PCR was performed using 150 ng cDNA product with SYBR Green PCR Master Mix (Qiagen) in 25 μL per PCR reaction according to the recommended conditions as previously described.…”
Section: Real-time Reverse-transcription Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation